2010
DOI: 10.1002/ibd.21287
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 receptor-associated kinase M downregulates DSS-induced colitis†

Abstract: This is the first report examining the role of IRAK-M in colitis. We find that IRAK-M is of critical importance in downregulating induction and progression of DSS colitis, and thereby suggesting that IRAK-M might be a target for future interventional therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 52 publications
(56 reference statements)
3
26
1
Order By: Relevance
“…Prior studies have evaluated Irak-m −/− mice in both dextran sulfate sodium (DSS) and Il10 −/− colitis models (Berglund et al, 2010, Biswas et al, 2011). These prior studies revealed that IRAK-M functions to attenuate the progression of experimental colitis (Berglund et al, 2010, Biswas et al, 2011). Here we utilized Irak-m −/− mice in an acute colitis model induced with 5% DSS (Okayasu et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have evaluated Irak-m −/− mice in both dextran sulfate sodium (DSS) and Il10 −/− colitis models (Berglund et al, 2010, Biswas et al, 2011). These prior studies revealed that IRAK-M functions to attenuate the progression of experimental colitis (Berglund et al, 2010, Biswas et al, 2011). Here we utilized Irak-m −/− mice in an acute colitis model induced with 5% DSS (Okayasu et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple mechanisms of negative regulation operate at different levels of the pathway to prevent over-activation of TLRs signaling. Intracellularly, the TLR signaling pathway can be regulated by cytoplasmatic molecules, such as MyD88s, IRAK-M, TOLLIP, and by activation of the PI3K/Akt pathway, among others (Arancibia et al 2011;Berglund et al 2010;Burns et al 2003;Kobayashi et al 2002;Zhang and Ghosh 2002). Extracellularly, soluble TLR (sTLR) behaves as a decoy receptor that counteracts receptor activation.…”
mentioning
confidence: 99%
“…SIGIRR knockout mice have normal susceptibility to systemic LPS toxicity but hyper-susceptibility to intestinal inflammation [94, 95], suggesting an intestinal specific role of SIGIRR in intestinal inflammation. IRAK-M is a negative regulator of TLR signaling [84], and IRAK-M is shown to down-regulate dextran sulfate sodium-induced colitis [96]. The colonic epithelial cells from ulcerative colitis patients express lower levels of PPARγ [85], while PPARγ ligand suppresses LPS-induced NF-κB promoter activity and dampens the inflammation in intestinal epithelial cells [97].…”
Section: Negative Regulators Of Tlr Signalingmentioning
confidence: 99%